2018
DOI: 10.1002/admi.201800852
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Liquid–Liquid Micropatterns through Guided Liquid Displacement on Liquid‐Infused Surfaces

Abstract: Here we demonstrate a method to pattern liquids of varying surface tension and composition into droplets by utilizing slippery liquid-infused surfaces prepared on chemically-patterned substrates. We study the capability of different liquids to displace the lubricant from higher surface energy regions and show that both high and low surface tension liquids can imbibe the polymer, thereby forming droplets sharply following underlying surface energy patterns. For all liquids tested, droplet arrays of arbitrary sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…C) Reproduced with pernmission. [83] Copyright 2018, wiley-VCH. D) Schematic of the structural architecture to combine slippery surfaces with superoleophobic double-reentrant structures.…”
Section: Patterned Slipsmentioning
confidence: 99%
See 1 more Smart Citation
“…C) Reproduced with pernmission. [83] Copyright 2018, wiley-VCH. D) Schematic of the structural architecture to combine slippery surfaces with superoleophobic double-reentrant structures.…”
Section: Patterned Slipsmentioning
confidence: 99%
“…energy patterns ( Figure 3C). [83] By changing the chemical patterning from fluorinated to aliphatic groups, patterns of mineral and silicone oils could be created. This method could be used to pattern perfluoro oils into designer-shape droplets, and to demonstrate formation of 2D micropatterns of threephase liquid systems (fluorinated, organic, and aqueous), which is usually difficult to achieve without superhydrophobicsuperoleophobic-hydrophilic patterns.…”
Section: Patterned Slipsmentioning
confidence: 99%
“…demonstrated the use of superhydrophobic–hydrophilic patterns to create designer multiphase droplets to confine an organic liquid droplet inside an aqueous droplet or for miniaturized liquid–liquid–liquid extraction application. [ 27,28 ] Other solid‐wall‐free strategies to confine liquids include embedding of water into a matrix of viscous poly(dimethylsiloxane) oil, [ 29,30 ] water–oil emulsions in microfluidic devices, [ 31,32 ] and aqueous channels held by immiscible magnetic liquid barriers. [ 33 ] With these strategies, however, only water can be confined.…”
Section: Introductionmentioning
confidence: 99%
“…Levkin et al also demonstrated droplet sorting and manipulation on chemically patterned lubricated slippery surfaces using two different lubricants corresponding to the two different regions of the chemical pattern. [24] They prepared millimeter-sized chemically patterned porous polymer surfaces to confine similar-sized drops, which slip preferably on a particular lubricating fluid over the other lubricant of the other region. The boundary between the chemically patterned regions and two different types of lubricants provided the energy barrier to confine and guide drops during gravity-driven motion.…”
Section: Introductionmentioning
confidence: 99%